2017
DOI: 10.18632/oncotarget.16133
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol, an activator of Sirtuin-3 (SIRT3) preserves mitochondria and protects the heart from doxorubicin-induced cardiomyopathy in mice

Abstract: Doxorubicin is the chemotherapeutic drug of choice for a wide variety of cancers, and cardiotoxicity is one of the major side effects of doxorubicin treatment. One of the main cellular targets of doxorubicin in the heart is mitochondria. Mitochondrial sirtuin, SIRT3 has been shown to protect against doxorubicin-induced cardiotoxicity. We have recently identified honokiol (HKL) as an activator of SIRT3, which protects the heart from developing pressure overload hypertrophy. Here, we show that HKL-mediated activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 67 publications
8
125
0
Order By: Relevance
“…Recent studies showed that SIRT3 exhibits mighty deacetylase activity and is the key regulator in organ protection under many pathologic states including inflammatory and oxidative stress, acting pivotal roles in development and progression of metabolic diseases including diabetes, neurodegenerative disorders, and other diseases . Honokiol (HNK), [2‐(4‐hydroxy‐3‐prop‐2‐enyl‐phenyl)‐4‐prop‐2‐enyl‐phenol], is a bioactive compound obtained from Magnolia grandiflora which possesses multiple properties including anti‐tumor, anti‐arrhythmic, anti‐thrombocytic, anti‐inflammatory, anti‐angiogenesis, anxiolytic, anti‐oxidative activities in vivo and in vitro . As a potent reactive oxygen species (ROS) scavenger, it is also reported that HNK can enhance the overexpression of SIRT3 to improve antioxidant activity and mitochondrial energy regulation thereby reducing the levels of Aβ and sAPPβ in Chinese Hamster Ovarian (CHO) cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that SIRT3 exhibits mighty deacetylase activity and is the key regulator in organ protection under many pathologic states including inflammatory and oxidative stress, acting pivotal roles in development and progression of metabolic diseases including diabetes, neurodegenerative disorders, and other diseases . Honokiol (HNK), [2‐(4‐hydroxy‐3‐prop‐2‐enyl‐phenyl)‐4‐prop‐2‐enyl‐phenol], is a bioactive compound obtained from Magnolia grandiflora which possesses multiple properties including anti‐tumor, anti‐arrhythmic, anti‐thrombocytic, anti‐inflammatory, anti‐angiogenesis, anxiolytic, anti‐oxidative activities in vivo and in vitro . As a potent reactive oxygen species (ROS) scavenger, it is also reported that HNK can enhance the overexpression of SIRT3 to improve antioxidant activity and mitochondrial energy regulation thereby reducing the levels of Aβ and sAPPβ in Chinese Hamster Ovarian (CHO) cells .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Honokiol (HNK), [2-(4- anti-oxidative activities in vivo and in vitro. [16][17][18][19][20][21] As a potent reactive oxygen species (ROS) scavenger, it is also reported that HNK can enhance the overexpression of SIRT3 to improve antioxidant activity and mitochondrial energy regulation thereby reducing the levels of Aβ and sAPPβ in Chinese Hamster Ovarian (CHO) cells. 22 Additionally, Xian et al suggested that HNK could improve learning and memory impairments induced by scopolamine in mice and attenuate the concentration of prostaglandin E2 and cyclooxygenase-2 level and the neuroinflammatory processes.…”
mentioning
confidence: 99%
“…One study has reported that SIRT-3 is decreased by DOX treatment due to the rise in ROS production and mitochondrial dysfunction. So, reducing SIRT-3 leads to elevation to ROS and HIF1α stabilization, which is an essential factor to shift metabolism from β-oxidation of fatty acid to glycolysis (the Warburg effect) [85]. Further, the inhibition of protein or slicing of the HIF1α gene has been suggested to decrease drug resistance against DOX [86].…”
Section: Doxorubicin's Effect On Myocardial Energy Metabolismmentioning
confidence: 99%
“…Honokiol, which is a polyphenol derived from magnolia tree, lessens cardiac hypertrophy and fibrosis by activating SIRT3 and protects cardiomyocytes from doxorubicin-induced cell destruction and death by promoting mitochondrial fusion and limiting mitochondrial ROS levels and mtDNA damage [99,100]. Adenovirus-mediated overexpression of SIRT3 might decrease pathogenesis of cardiovascular diseases by inhibition of Dox-induced cardiac hypertrophy and mitochondrial defects.…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 99%